2003
DOI: 10.2113/gscanmin.41.6.1363
|View full text |Cite
|
Sign up to set email alerts
|

DISORDERED Mg-BEARING OLENITE FROM A GRANITIC PEGMATITE AT GOSLARN, AUSTRIA: A CHEMICAL, STRUCTURAL, AND INFRARED SPECTROSCOPIC STUDY

Abstract: The core and rim of a short prismatic dark brown tourmaline crystal (10 mm in diameter) from a granitic pegmatite near Goslarn, Lower Austria, were structurally and chemically characterized, including H 2 O determination and Mössbauer analysis. The optimized formula, calculated using chemical and structural data for the core, is X (Na 0 , which can be assigned to O-H1 stretching, is relatively small. This is in agreement with the occupancy of ~[O 0.9 (OH) 0.1 ] at the W site. We assess the assignment of Mg-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 11 publications
(32 reference statements)
1
20
0
Order By: Relevance
“…MacDonald and Hawthorne (1995) have shown that <T-O> distances in uvite, ideally Ca(Mg,Fe 2+ ) 3 (MgAl 5 )Si 6 O 18 (BO 3 ) 3 (F,OH) 4 , are in accord with the occurrence of Al at the T site, and structural work on other compositions (Bloodaxe et al 1999;Schreyer et al 2002;Cempírek et al 2006;Prowatke et al 2003;Ertl and Hughes 2002;Ertl et al 2003) also show small amounts of Al at the T site.…”
Section: Previous Workmentioning
confidence: 94%
“…MacDonald and Hawthorne (1995) have shown that <T-O> distances in uvite, ideally Ca(Mg,Fe 2+ ) 3 (MgAl 5 )Si 6 O 18 (BO 3 ) 3 (F,OH) 4 , are in accord with the occurrence of Al at the T site, and structural work on other compositions (Bloodaxe et al 1999;Schreyer et al 2002;Cempírek et al 2006;Prowatke et al 2003;Ertl and Hughes 2002;Ertl et al 2003) also show small amounts of Al at the T site.…”
Section: Previous Workmentioning
confidence: 94%
“…There has been considerable work done on the characterization (e.g. Hawthorne et al, 1993;Burns et al, 1994;Taylor et al, 1995;Dyar et al, 1998;Francis et al, 1999;Bloodaxe et al, 1999;Kalt et al, 2001;Cámara et al, 2002;Schreyer et al, 2002;Ertl and Hughes, 2002;Ertl et al, 2003aErtl et al, ,b, 2004Ertl et al, , 2005Hughes et al, 2000Marschall et al, 2004;Bosi et al, , 2005 and understanding (Hawthorne, 1996(Hawthorne, , 2002 of site occupancy in tourmaline. However, the complete derivation of site populations (and accurate bulk compositions) is not trivial, and our knowledge of the crystal chemistry of all the tourmaline minerals is still far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…The structure refi nement and chemical data obtained in this study by that method yields a structural formula for this synthetic Ag-bearing tourmaline of: In reference to tourmaline end-member species (Hawthorne and Henry 1999), we can describe this tourmaline as a mixture of olenite (51 mol%) and dravite (49 mol%). Hence, this tourmaline belongs to the olenite-dravite series as do the tourmaline samples described by Ertl et al (2003a). Refi ning Na ↔ Ag at the X site clearly indicates that Ag occupies this site (Table 3).…”
Section: Crystal Structurementioning
confidence: 73%
“…Substitution of Al for Mg at the Z site has been described by , Hawthorne et al (1993), MacDonald and Hawthorne (1995), Taylor et al (1995), Bloodaxe et al (1999), andErtl et al (2003a). Signifi cant amounts of Mg at the Z site are refl ected in the <Z-O> distance.…”
Section: Crystal Structurementioning
confidence: 94%